2017
DOI: 10.1111/odi.12689
|View full text |Cite
|
Sign up to set email alerts
|

LTF and DEFB1 polymorphisms are associated with susceptibility toward chronic periodontitis development

Abstract: Our results suggest the involvement of DEFB1 and LTF genetic variations in the susceptibility toward development of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 59 publications
0
27
2
Order By: Relevance
“…A total of 41 citations were determined and of these seven case-control studies met the inclusion criteria (Wohlfahrt et al, 2006; Ozturk et al, 2010; Schaefer et al, 2010; Loo et al, 2012; Ikuta et al, 2015; Ma, 2016; Zupin et al, 2017). Figure 1 presented the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 41 citations were determined and of these seven case-control studies met the inclusion criteria (Wohlfahrt et al, 2006; Ozturk et al, 2010; Schaefer et al, 2010; Loo et al, 2012; Ikuta et al, 2015; Ma, 2016; Zupin et al, 2017). Figure 1 presented the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Yadav et al () also reported a higher LTF level in the periodontitis patients than in the healthy controls, and LTF quantification could reduce after periodontal therapy. Gene polymorphisms influence the concentration and activity of LTF, Zupin et al () observed an association between rs1126477 and risk of chronic periodontitis, among 439 North‐Eastern Italian subjects, possibly because of the influence of these loci on the antibacterial activity of LTF. Jordan indicated that the frequency of LTF rs1126477 G allele was higher in patients with aggressive periodontitis, suggesting that this polymorphism was associated with aggressive periodontitis in an African American, but not a Caucasian population (Jordan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the tag single nucleotide polymorphisms (SNPs) were selected according to the following points: (a) minor allele frequency (MAF) exceeding 5%; (b) SNPs with functional effects on protein coding, splicing and transcriptional regulation, which were possibly directly associated with disease (Lee & Shatkay, ); and (c) SNPs which were previously studied in oral diseases including caries (Wu et al, ; Zupin et al, ). Fine at el.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence that periodontitis is a complex multifactorial disease has led to the study of host susceptibility risk factors that could potentially predispose to this pathology as well as to the different clinical phenotypes. Different genetic variations were previously identified as potential factors involved in its development and among them, various works investigated the role of MHC [reviewed in]. Different genes in the MHC locus, just centromeric to the class I region, were previously associated with periodontitis, such as, for example, TNF‐ α, BAT1, NFKBL1 and LTA (encoding for tumour necrosis factor (TNF)‐α, HLA‐B‐associated transcript 1, nuclear factor of κ light chain gene enhancer in inhibitor‐like 1 B cells, lymphotoxin alpha (LTα), respectively).…”
Section: Introductionmentioning
confidence: 99%